Assessment on the Characterization of Mineralogical Phase of Ceramic Tiles Available in Kathmandu Valley (Nepal) Using XRD and FTIR Analyses - Budhathoki, Pramod; Paudyal, Gopal; Oli, Rishiram; Duwal, Nirjan; Bhattarai, Jagadeesh (International Journal of Applied Sciences and Biotechnology, 2018)
The mineralogical phase of eight different types of contemporary and historical ceramic tile samples used in Kathmandu valley of Nepal was analyzed using their X-ray diffraction (XRD) patterns and Fourier transform infrared (FTIR) spectra to assess their quality. Mineralogical phases existed in these eight different tile samples, i. e., three wall, three floor and two ancient tile sample specimens, used in this study are identified as quartz, feldspars, spinel, mullite and hematite including paragonite with the help of the corresponding Joint Committee for Powder Diffraction Standards (JCPDS) database files. The firing temperature applied during the time of these ceramic tiles production should be 1000° C or slightly more. The mineralogical compositions of the contemporary tile samples are found to be comparable with those of the ancient brick samples of the historical temples and monuments of Kathmandu valley of Nepal. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 238-243